A Salamon trónja, a Targum Sheni Eszter tükrében - János MÁRTON (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2024)
The Throne of Solomon as Reflected in Targum Sheni. The Hebrew and Aramaic targum means ‘translation’, ‘variant’. They are extremely readable, if only because they are not literal translations but also include an explanation of the text, including aggadic material from various rabbinic sources. In the Second Temple period, Aramaic as a spoken language slowly superseded Hebrew. Although we do not know when exactly when this shift took place, but we can be sure that by the Second Temple period it had become sacralized and was on a par with Hebrew. The description of the throne of Solomon has a theological role to play in describing Solomon’s reign of peace. The king’s wisdom is also reflected in the fact that, according to the Targum, he understands the language of the animals and controls them. The throne in its fullness is nothing more than an expression of wealth and splendour, which in turn refer to the King of Kings: God. And its mysterious workings suggest that the Creator God, the redeemed, is allowed to create mysterious things that no one else can ever replicate. That is why the description concludes, “This is King Solomon’s throne, the like of which has never been seen in all the world.”